2017
DOI: 10.1080/13854046.2017.1288269
|View full text |Cite
|
Sign up to set email alerts
|

When synesthesia and savant abilities are mistaken for hallucinations and delusions: contribution of a cognitive approach for their differential diagnosis

Abstract: In complex cases, neuropsychological and formal evaluations are necessary to establish a differential diagnosis. Moreover, the case highlights the link between synesthesia and savant abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…by experiences in which a perceptual presence or real-world perceptual veridicality is lacking. By examining synaesthesia, a perceptual phenomenon in healthy humans distinct from psychopathological delusions or hallucinations [10], we show behavioural effects and identify plausible neuronal correlates of how this is possible. Graphemecolour synaesthesia is a condition in which single digits, letters and words (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by experiences in which a perceptual presence or real-world perceptual veridicality is lacking. By examining synaesthesia, a perceptual phenomenon in healthy humans distinct from psychopathological delusions or hallucinations [10], we show behavioural effects and identify plausible neuronal correlates of how this is possible. Graphemecolour synaesthesia is a condition in which single digits, letters and words (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…is non-veridical) [9]. Thereby, synaesthesia can clearly be differentiated from hallucinations and delusions associated with psychopathology or drug-induced states, and can serve as a useful tool for studying the underlying neurophysiology of healthy non-veridical perceptions relevant to the higher-order cognitive control of action [10,11]. Using synaesthesia as a model condition, we show how non-pathological perceptual feature dimensions that are not objectively perceived as present in the real world (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…by experiences in which a perceptual presence or real-world perceptual veridicality is lacking. By examining synaesthesia, a perceptual phenomenon in healthy humans distinct from psychopathological delusions or hallucinations (Bouvet et al, 2017), we detail the mechanisms how this is possible. Grapheme-colour synaesthesia is a condition in which single digits, letters and words (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…is nonveridical or illusory) (Seth, 2014). Thereby, synaesthesia can clearly be differentiated from hallucinations and delusions associated with psychopathology, and can serve as a useful tool for studying the underlying neurophysiology of healthy non-veridical perceptions relevant to the higher-order cognitive control of action (Sagiv and Frith 2013;Bouvet et al 2017). Using synaesthesia as a model condition, we show how non-pathological perceptual feature dimensions that are not objectively perceived as present in the real world (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Nakagami et al (2020) found that patients with anti-PDHA1 antibodies had increased volumes of the left occipital fusiform gyrus and left cuneus, a finding that is in contrast to the decreased volumes typically seen in SSD patients in comparison to controls (Nakagami et al, 2020). Increased volumes of fusiform gyrus have been previously associated with synesthesia -a disorder characterized by abnormal perception in response to the presence or absence of an external sensory stimulus -which can potentially be linked to an underlying common mechanism for hallucinations and delusions typical of SSD (Bouvet et al, 2017;Hupé et al, 2015;Weiss et al, 2009). PDHA1 dysfunction has been associated with mitochondrial dysfunction, as well as numerous neuropsychiatric disorders, including Parkinson's disease, dementia, psychosis and SSD (Nakagami et al, 2020).…”
Section: Prevalence Of Treatable Genetic Disorder Variants Within the Study Cohortmentioning
confidence: 99%